INTERNATIONAL COLLABORATION ON ENGLISH TEXTBOOKS FOR GEORGIAN UNIVERSITY STUDENTS - Farina, Donna M.; Rusieshvili, Manana (Online Journal of Humanities ETAGTSU, 2021)
This article describes the process of creation of a series of textbooks to assist students in developing and enhancing their listening, speaking, reading, and listening skills in English. The textbooks are being written as a result of extensive cooperation between Georgian colleagues and American specialists from several universities. The article focuses on a reading textbook (working title: Read in English Outside the Box), being written through an ongoing collaboration between the Tbilisi State University team led by Professor Manana Rusieshvili, and Professor Donna Farina from New Jersey City University, USA. Full Text (PDF)